Naïve realism and the phenomenology of perception and memory (Acta Scientiarum. Human and Social Sciences, 2022)
In this paper, I begin to explore what a naïve realist might say about the phenomenology of episodic memory. I start by arguing that, when it comes to accounting for the phenomenology of memory experiences, there are two primary options available to the naïve realist: to treat memory phenomenology along the same lines as perceptual phenomenology – as involving phenomenal character that is grounded in acquaintance with the external environment – or to treat memory as lacking such acquaintance-based phenomenal character, and then attempting to account for there being something it is like to remember as being somehow inherited from cases that do have phenomenal character. I then explore the prospects of providing an account of the phenomenology of episodic memory in both ways, before tentatively coming down in favour of the latter approach